Alternative revisions of the 𝘈𝘮𝘦𝘳𝘪𝘤𝘢𝘯 𝘚𝘵𝘢𝘯𝘥𝘢𝘳𝘥 𝘝𝘦𝘳𝘴𝘪𝘰𝘯 (1901) and retranslations within the Tyndale–King James Version tradition - Naudé, Jacobus A.; Miller-Naudé, Cynthia L. (AOSIS Publishing, 2022)
In this essay, we demonstrate that in addition to the Revised Standard Version and its revisions as part of the linear emergence of the Tyndale–King James Version tradition in the 20th and 21st centuries, there are also alternative revisions and retranslations of the 𝘒𝘪𝘯𝘨 𝘑𝘢𝘮𝘦𝘴 𝘝𝘦𝘳𝘴𝘪𝘰𝘯 (KJV) of 1611 as literal or word-for-word translations, which emerge as divergent branches. The revisions of the 𝘈𝘮𝘦𝘳𝘪𝘤𝘢𝘯 𝘚𝘵𝘢𝘯𝘥𝘢𝘳𝘥 𝘝𝘦𝘳𝘴𝘪𝘰𝘯 (ASV) (1901) emerged in the following branches, namely the 𝘕𝘦𝘸 𝘈𝘮𝘦𝘳𝘪𝘤𝘢𝘯 𝘚𝘵𝘢𝘯𝘥𝘢𝘳𝘥 𝘉𝘪𝘣𝘭𝘦 (NASB) and its revisions, 𝘛𝘩𝘦 𝘈𝘮𝘱𝘭𝘪𝘧𝘪𝘦𝘥 𝘉𝘪𝘣𝘭𝘦 (AB) and its revisions, as well as 𝘛𝘩𝘦 𝘓𝘪𝘷𝘪𝘯𝘨 𝘉𝘪𝘣𝘭𝘦, Paraphrased and its retranslation, the 𝘕𝘦𝘸 𝘓𝘪𝘷𝘪𝘯𝘨 𝘛𝘳𝘢𝘯𝘴𝘭𝘢𝘵𝘪𝘰𝘯 (NLT). Then there are revisions that emerged as alternatives to the 𝘙𝘦𝘷𝘪𝘴𝘦𝘥 𝘚𝘵𝘢𝘯𝘥𝘢𝘳𝘥 𝘝𝘦𝘳𝘴𝘪𝘰𝘯 (1946–1952/1971) by reverting to the 𝘒𝘪𝘯𝘨 𝘑𝘢𝘮𝘦𝘴 𝘙𝘦𝘷𝘪𝘴𝘦𝘥 (Blayney) Edition (1769) as their incipient text rather than the ASV, namely 𝘛𝘩𝘦 𝘔𝘰𝘥𝘦𝘳𝘯 𝘒𝘪𝘯𝘨 𝘑𝘢𝘮𝘦𝘴 𝘝𝘦𝘳𝘴𝘪𝘰𝘯 (MKJV) (and similar revisions), The 𝘕𝘦𝘸 𝘒𝘪𝘯𝘨 𝘑𝘢𝘮𝘦𝘴 𝘝𝘦𝘳𝘴𝘪𝘰𝘯 (NKJV) and the 𝘕𝘦𝘸 𝘊𝘢𝘮𝘣𝘳𝘪𝘥𝘨𝘦 𝘗𝘢𝘳𝘢𝘨𝘳𝘢𝘱𝘩 𝘉𝘪𝘣𝘭𝘦. Finally, there are retranslations within the Tyndale–King James Version tradition, namely the 𝘊𝘰𝘯𝘵𝘦𝘮𝘱𝘰𝘳𝘢𝘳𝘺 𝘌𝘯𝘨𝘭𝘪𝘴𝘩 𝘝𝘦𝘳𝘴𝘪𝘰𝘯 (CEV), and the 𝘊𝘰𝘮𝘮𝘰𝘯 𝘌𝘯𝘨𝘭𝘪𝘴𝘩 𝘉𝘪𝘣𝘭𝘦 (CEB). The diversity reflects the search for individual identity to satisfy particular reader expectations in an age of digital-media interpretive culture featuring broad universal values. 𝗖𝗼𝗻𝘁𝗿𝗶𝗯𝘂𝘁𝗶𝗼𝗻: Instead of viewing the revisions and retranslations within the Tyndale–King James Version tradition since the second half of the 20th century as new and independent, it is demonstrated that the various branches and their versions rather continue the emergence of the pre-20th century translation complex within this tradition to satisfy particular reader expectations.
Keywords: King James Version; American Standard Version; Contemporary English Version; Common English Bible; Living Bible; New Living Translation; New American Standard Bible